1972
DOI: 10.1098/rspb.1972.0045
|View full text |Cite
|
Sign up to set email alerts
|

The development of the labyrinth of the lamprey ( Lampetra fluviatilis Linn. 1758)

Abstract: The development of the labyrinth of Lampetra fluviatilis was investigated on three levels; the development of the gross morphology, the development of the hair cell orientation within the sensory areas, and the subcellular development of the sensory cells. The mode of development of the semicircular canals was found to differ from that found in gnathostomes. The hair cell orientation is derived from a sensory rudiment that has a complex orientation. The adult form is derived from this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1974
1974
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…The FITC-phalloidin stain revealed that lamprey hair cells have a substantial infracuticular network of actin penetrating into the hair cell body (Fig. 5B), which may correspond to the striated organelle described by Thornhill (Thornhill, 1972). This is not found in zebrafish hair cells, but a similar network has been described in guinea pig hair cells (Carlisle et al, 1988;…”
Section: Distinct Regions Of the Lamprey Macula Communis Correspond Tmentioning
confidence: 83%
See 4 more Smart Citations
“…The FITC-phalloidin stain revealed that lamprey hair cells have a substantial infracuticular network of actin penetrating into the hair cell body (Fig. 5B), which may correspond to the striated organelle described by Thornhill (Thornhill, 1972). This is not found in zebrafish hair cells, but a similar network has been described in guinea pig hair cells (Carlisle et al, 1988;…”
Section: Distinct Regions Of the Lamprey Macula Communis Correspond Tmentioning
confidence: 83%
“…1). Adult lamprey inner ears have only two semicircular canals, each with a tricuspid crista, and a single ventrally positioned macula communis that covers the floor of two joined, symmetrical, ciliated chambers (de Burlet and Versteegh, 1930;Lowenstein et al, 1968;Thornhill, 1972;Avallone et al, 2005). A similar pattern, with two semicircular canals, is found in the abundant agnathan fossil record, making it likely that this represents the ancestral condition (Mazan et al, 2000).…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations